Optimalisasi produk UMKM melalui pelatihan desain logo dan kemasan di Desa Kalijambe Kecamatan Bringin Kabupaten Semarang - Muafidah, Zahrotul; Rohman, Taufiqur; Arofah, Erika Afifatul; Prabawa, Abi Fa’izzarahman (Nur Science Institute, 2024)
In the business world in Indonesia, many problems are currently being faced, one of which is intense product competition in the marketing realm with large companies whose products meet quality standards. The need for more expertise of MSMEs (micro, small, and medium enterprises) in improving product quality is the cause of this problem. This study aims to provide training on optimizing MSME products through logo design and product packaging. The method used is PAR (Participatory Action Research), which involves planning, action, observation, and reflection stages. The number of subjects was 24 MSME actors in Kalijambe Village. KKN students took the initiative to hold logo and packaging design training by inviting entrepreneurship experts and academics from UIN Salatiga, and the result was that MSMEs in Kalijambe Village, whose product packaging was initially less attractive, became more attractive.